Reports of International Arbitral Awards, Vol. XXX - United Nations (United Nations, 2012)
This publication was conceived in 1948 as a collection of international awards or decisions rendered between States, including cases involving espousing or respondent Governments on behalf of individual claimants. The present volume reproduces the awards in two arbitration cases, namely, the case between Guyana and Suriname concerning the delimitation of their shared maritime boundary, and the case between the Government of Sudan and the Sudan People’s Liberation Movement/Army regarding the delimitation of the Abyei Area. The volume also includes two tables providing a comprehensive listing, in alphabetical and chronological order, respectively, of all the cases published in volumes I to XXX